Program Szczepień Ochronnych w 2017 roku - powszechne szczepienia przeciwko pneumokokom u dzieci - Jackowska, Teresa; Bernatowska, Ewa (Pediatria Polska - Polish Journal of Paediatrics, 2017)
In Poland, starting from 2017, mandatory vaccination against pneumococcus in children will be financed. There are two conjugate vaccines: PCV10 and PCV13 for children from 2 months of age. PCV10 vaccine was purchased for mandatory vaccination programme. In 2011-2015, PCV13 vaccine in children provided more than 20% broader serotypes coverage than the PCV10 vaccine (www.koroun.edu.pl). PCV13 is the only vaccine that demonstrated protection against invasive and non-invasive diseases caused by serotype 19A, which is the most common multi-drug resistant serotype in the population (approximately 80% of the isolates of 19A are MDR). Serotype 19A was the third most common serotype after 6B and 14, responsible for invasive pneumococcal disease (IPD) in children up to 2 years of age. The vaccine PCV10 does not include antigen of serotype 19A. In Kielce, over the last 10 years of the universal immunization programme, PCV7 / PCV13 in children showed reduction in carriage of penicillin-resistant serotypes of Streptococcus pneumoniae. Indirect effect as a decrease in pneumonia in non-vaccinated elderly population has been observed. Pediatric Group of Experts on the Immunization Programme by the Ministry of Health, based on the Polish data KOROUN, recommended vaccine PCV13 for the implementation as universal immunization for children. The arguments for the recommendation take into account the broadest serotype coverage, reducing the carriage of antibiotic-resistant serotypes and the impact of PCV13 vaccine to reduce pneumonia in non-vaccinated population. Vaccination in high-risk groups, including preterm newborns, remains unchanged. For this group, PCV13 is recommended.